Islam Nusantara: An integration opportunity between Christianity and culture in Indonesia - Hutagalung, Stimson (HTS teologiese studies, 2022)
The integration or inculturation of religion and culture has been massively and controversially discussed despite being successfully presented by Islam Nusantara. Therefore, this study attempts to delve into the possibilities of integrating Christianity into the culture of Indonesia by seeking the Islam Nusantara experience. The study employed a qualitative method, using literature, articles, books and related references, and attempted to reconstruct the Islamic dimension concerning inculturation. Subsequently, the opportunity for Christianity will be displayed and formulated to establish a hospitable religion. This will offer a chance to improve and develop its identity regarding integration into the local culture by respecting without destroying, contextualising without syncretising and negotiating without compromising.Contribution: This article contributes to the ongoing debates on culture and Christianity in Indonesia. Islam Nusantara offers an opportunity and example of how religion and culture should collaborate. The expectation is that the collaboration will display a solid formation to other contexts in Asia or Africa that could arrange a fruitful conversation between culture and Christianity.